Sosialisasi Prinsip 5S di Dapur UMKM Katering Depok - Masri Pradipto; Tri Novita Sari; Sri Hartini; Fatoni Fatoni; Mohammad Riski Borman (Pusat Riset dan Inovasi Nasional, 2024)
Depok Catering UMKM is one of the UMKMs in Depok, West Java which operates in the field of providing food for homes, schools, offices or other agencies. Depok Catering MSMEs often experience problems in the form of delivering food orders to customers within the given deadline. This is because the condition of the kitchen is untidy, disorganized and workers have low awareness of paying attention to aspects of neatness and order. Workers need more time to look for the cooking utensils they need, cooking utensils that are not cleaned immediately and are left dirty anywhere, or cooking utensils that are placed haphazardly and not in their storage place. This problem causes waste. To overcome one of the wastes, you can use the 5S method. This outreach activity aims to provide understanding and views about the importance of implementing 5S and its positive impact on catering businesses. The questionnaire was given to determine understanding of the 5S Principles. As many as 20% of participants had never heard or knew about the 5S Principles. Socialization activities make workers know, understand and apply the 5S Principles.